Taxes et redevances dans le transport routier de marchandises: Analyse succincte et tableaux de données 1998-2012 - Bertil Hylén; Jari Kauppila; Edouard Chong (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
– This paper updates the database on heavy goods vehicle charges and taxes in Europe, with figures for 2012 on taxes and charges on vehicles, fuel and road use, including relevant information on rebates and exemptions. A short analysis of the level of charges and expected future developments is included. Data are collected for nearly 30 countries. A brief discussion of similar taxes and charges in the United States, Canada and Australia is included as well. The VTI library is the source for most of the information on these countries. The first step was to prepare an inventory of existing taxes and charges. This inventory is based mainly on a questionnaire forwarded to the respective Ministries of Transport or the responsible government agencies. Other sources include websites for ministries and toll operators. These data are used to analyse the fiscal and territorial structure of the charges. In order to allow for comparisons of road freight taxation regimes in different countries, net taxation levels are calculated for a standard domestic haul. These results are then assessed per vehicle-km and per tonne-kilometre.
Keywords: 330